The The CERDAS App for Screening Adolescent Mental Health Problems: A Usability Test - septiana, Nenty; Zahratul LIza, Suci; Kamaly, Nurul (STIKES Suaka Insan, 2025)
Adolescent mental health is becoming increasingly serious, affecting adolescents' ability to learn. One of the areas that need special emphasis is the use of an innovative website-based CERDAS app as an initial screening of adolescent mental health. The purpose of this study is to determine the CERDAS app usability as an initial screening tool for adolescent mental health. The study's design is descriptive with a cross-sectional approach. Simple random sampling was used to pick 94 respondents for the study. mental health of adolescents. Evaluate the usability of the CERDAS app using a website user satisfaction questionnaire developed by Handayani (2014). It contains 15 question items divided into four aspects: ease of use, customized, download delay, and content. This questionnaire has been valid and reliable. Data analysis used frequency distribution and percentage to describe the usability of the CERDAS app. The results showed that the CERDAS app was very useful, with with 84.4% ease-of-use, 89.3% customized, 86.9% download delay, and 89.9% content.The CERDAS app is a very useful tool for screening the mental health of adolescenst. The development of features for techniques for managing mental health problems will likely improve adolescent mental health.